Protecting Rice Grains in the Post-Genomic Era 2019
DOI: 10.5772/intechopen.84882
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Strategies for Managing Bacterial Panicle Blight in Rice

Abstract: Bacterial panicle blight (BPB) is present in more than 18 countries and has become a global disease in rice. BPB is highly destructive and can cause significant losses of up to 75% in yield and milling quality. BPB is caused by Burkholderia glumae or B. gladioli, with the former being the primary cause of the disease. Outbreaks of BPB are triggered by conditions of high temperatures in combination with high relative humidity at heading. The disease cycle starts with primary infections from infected seed, soil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…Advances in DNA marker technology have sped up the identification of resistant cultivars carrying resistance gene(s) (Nor'Aishah et al, 2013). Till now, about 34 genes (23 dominants and 16 recessive genes) conferring resistance to bacterial leaf blight have been identified (Zhou, 2019). By using DNA markers, numerous commercial rice varieties have been introgressed with race-specific resistance genes including xa4, xa5, xa7, xa13, and xa21 and improved their resistance against Xoo (Bharani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in DNA marker technology have sped up the identification of resistant cultivars carrying resistance gene(s) (Nor'Aishah et al, 2013). Till now, about 34 genes (23 dominants and 16 recessive genes) conferring resistance to bacterial leaf blight have been identified (Zhou, 2019). By using DNA markers, numerous commercial rice varieties have been introgressed with race-specific resistance genes including xa4, xa5, xa7, xa13, and xa21 and improved their resistance against Xoo (Bharani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of yellow toxoflavin hue in B. glumae is a virulence agent that causes grain rot on rice. Some avirulent strains have been isolated from symptomatic rice grains [21,22]. However, these strains could not generate toxoflavin [10].…”
Section: Anaerobic Growthmentioning
confidence: 99%
“…Only a limited number of cultivars with partial resistance are available and no chemical control measure is available in the U.S. Although oxolinic acid has been used for BPB control in other countries [ 22 ], this antibiotic is not labeled for use on rice in the U.S. [ 23 ]. Due to the absence of highly effective pesticides and increasing outbreaks of BPB, it is imperative to develop BPB-resistant cultivars [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of highly effective pesticides and increasing outbreaks of BPB, it is imperative to develop BPB-resistant cultivars [ 24 ]. In the U.S. alone, more than 200 elite breeding lines and cultivars were evaluated for BPB [ 23 ]. Results of multiple years of evaluations revealed that most of the U.S. rice cultivars are highly susceptible to BPB and there is no promising resistant line available yet [ 25 ].…”
Section: Introductionmentioning
confidence: 99%